1997
DOI: 10.1007/pl00009517
|View full text |Cite
|
Sign up to set email alerts
|

Mealtime Difficulties in a Home for the Aged: Not Just Dysphagia

Abstract: A mealtime screening tool was administered to 349 residents of a home for the aged to determine the prevalence of mealtime difficulties including, but not limited to, dysphagia. Mealtime difficulties, as assessed during a single meal observation of each resident, were documented in 87% of these individuals. Though 68% exhibited signs of dysphagia, 46% had poor oral intake, 35% had positioning problems, and 40% exhibited challenging behaviors. An increased prevalence of mealtime difficulties was related to both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
2
16

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(148 citation statements)
references
References 16 publications
4
125
2
16
Order By: Relevance
“…It was reported that 87% of residential care clients who are predominantly elderly had a symptom of dysphagia with mealtime difficulties which is associated with gastroenterological dysfunction. 1 The rate of disordered swallowing was higher in the aged population. 2,3 Several studies showed decreased sphincter relaxations and decreased esophageal contraction and dilatation in the aged people.…”
Section: Introductionmentioning
confidence: 94%
“…It was reported that 87% of residential care clients who are predominantly elderly had a symptom of dysphagia with mealtime difficulties which is associated with gastroenterological dysfunction. 1 The rate of disordered swallowing was higher in the aged population. 2,3 Several studies showed decreased sphincter relaxations and decreased esophageal contraction and dilatation in the aged people.…”
Section: Introductionmentioning
confidence: 94%
“…Swallowing disorders (dysphagia) are common among people who have had strokes (Murry et al, 1999); clinical signs of swallowing difficulty have been observed in as many as 70% of institutionalized older people (Steele et al, 1997). People with dysphagia are at risk for choking, aspiration (entry of material into the airway), and inadequate nutritional intake; airway obstruction, aspiration pneumonia, and malnutrition are serious consequences.…”
Section: Eatingmentioning
confidence: 99%
“…Nutrition and food services advancements are required to ensure: menus that consider the needs of the substantial proportion of long stayers, dining environments (eg, bistro or dining room in contrast to bed), meal-time atmosphere, 15,16 proximity of meal choice to delivery, 17 dense meals, [18][19][20] assistance with meals, [21][22][23] nursing staff involvement in meal times, 24 early identification and intervention for those at nutritional risk, 25 and ease of access to nutritional supplements. 26 Supplementation has not been found to reduce other oral intake.…”
Section: Implications For Nutrition and Food Servicesmentioning
confidence: 99%